A holistic approach to the problem of Rheumatoid Arthritis in geriatric patients - Szmelcer, Beniamin; Topka, Weronika; Wszelaki, Patrycja; Wilczyński, Michał; Porada, Mateusz; Florczak, Aleksander; Modrzejewski, Mateusz; Wąsicki, Mariusz; Wysocka, Oktawia; Cięszka, Karolina; Szewczak, Dorota; Kujawska, Agnieszka; et al. (Journal of Education, Health and Sport, 2019)
Rheumatoid arthritis is a chronic disease and belongs to the group of systemic connective tissue diseases having an autoimmune basis. The most commonly reported symptoms by patients are pain, swelling and difficulty moving the affected joints. The course of rheumatoid arthritis is different in the elderly, the onset of the disease in the elderly is more severe than in the young, and large proximal joints are primarily involved. Make a diagnosis as soon as possible and start treatment, the greater the chance of delaying disease progression and even remission, which will minimize disability. In the treatment of rheumatoid arthritis in the elderly, who often have co-morbidities and often mobility difficulties, the role of physiotherapist and nursing care is extremely important next to medical treatment. The use of kinesitherapy allows you to increase the range of motion of the joints and maintain them in good functional condition. Physiotherapy, on the other hand, has analgesic and anti-inflammatory effects. This effect is enhanced by properly selected pharmacological treatment, carried out with the help of disease-modifying drugs, anti-inflammatory drugs, glucocorticosteroids and biological drugs.